Case report and literature review: A de novo pathogenic missense variant in ACTN4 gene caused rapid progression to end-stage renal disease - He, Zhechi; Wu, Ke; Xie, Wenqing; Chen, Jianghua (Frontiers in Pediatrics, 2022)
Background: Focal segmental glomerulosclerosis (FSGS) is a histopathological diagnosis of the sclerosis of glomeruli and the damage to renal podocytes. FSGS process affects the filtration function of the kidney, which results in nephrotic syndrome (NS) in children and adults. FSGS is a clinically and genetically heterogeneous disorder representing a spectrum of hereditary renal diseases. Focal segmental glomerulosclerosis-1 (FSGS-1) [MIM:603278] is one of progressive renal diseases, which caused by heterozygous variants of the actinin alpha 4 (ACTN4) [MIM:604638] on chromosome 19q13.2 in dominant inheritance manner. With the recent development of whole-exome sequencing (WES), twenty-two (including our case) pathogenic or likely pathogenic ACTN4 gene variants have been identified for now. Case Presentation: We reported a 17-year-old Chinese girl hospitalized with foamy urine, nausea and vomiting. Laboratory tests revealed elevated levels of serum creatinine, urine proteinuria and urea nitrogen. Ultrasonography revealed bilateral reduced kidneys. The primary diagnosis were nephrotic syndrome (NS) and chronic kidney disease stage 5 (CKD5). Her kidney disease progressed rapidly to end-stage renal disease (ESRD) within 3 weeks. The hemodialysis was initiated 48 hours after admission and primary diagnosis. The hemodialysis continued for 4 months until the patient received allogeneic kidney transplantation from her father. A novel heterozygous missense ACTN4 gene variant c.494C>T (p.A165V) was found by whole-exome sequencing (WES) in the patient and confirmed by Sanger sequencing. Conclusions: The novel heterozygous missense variant was pathogenic, causing the rapid progression to ESRD. It should be noted that the severe proteinuria at early onset and rapid progression to ESRD are important and characteristic symptoms of ACTN4 variants related with FSGS and genetic screening is recommended if necessarily.